Increasing the Students’ Writing Skill in Recount Text through Snowball Throwing Method at the Tenth Grade of SMK Negeri 1 Gunungsitoli Barat in 2022/2023 - Selfi Krisna Yanti Zebua; Elwin Piarawan Zebua; Yasminar Amaerita Telaumbanua; Hidayati Daeli (Edumaspul: Jurnal Pendidikan, 2023)
Writing is one of the important skills that must be learnt by the students. However, the students had several problems in learning writing which caused the MCC were not able to achieve by the students especially in writing recount text. They were the students were lack of vocabulary, the lack of students in organizing ideas, the students were not able to use verb and grammar correctly, and students were not able to identify the generic structure of recount text. Therefore, the aim of research was to increase the students’ writing skill in recount text through Snowball Throwing Method. The research was conducted by using Classroom Action Research (CAR) and it was applied in two cycles. Each cycle consisted of several procedures namely planning, action, observation, and reflection. The result of Cycle I showed that most of the students were not able to achieve MCC where no student in “Excellent” level (0%), 4 students in “Good” level (22.22%), 10 students in “Fair” level (55.56%), and 4 students in “Poor” level (22.22%). The average of students’ writing skill in Cycle I was 65.78. While the result of Cycle II showed that all of students have been achieved MCC where 13 students in “Excellent” level (72.22%), 5 students in “Good” level (27.78%), and there was no student in “Fair” level and “Poor” level. The average of students’ writing skill in Cycle II was 80.89. Based on the result above, it proved that Snowball Throwing Method increases the students’ writing skill in recount text.